Capsule Biosynthesis and Basic Metabolism in Streptococcus pneumoniae Are Linked through the Cellular Phosphoglucomutase - Hardy, Gail G. (American Society for Microbiology (ASM), 2000)
Synthesis of the type 3 capsular polysaccharide of Streptococcus pneumoniae requires UDP-glucose (UDP-Glc) and UDP-glucuronic acid (UDP-GlcUA) for production of the [3)-β-d-GlcUA-(1→4)-β-d-Glc-(1→](n) polymer. The generation of UDP-Glc proceeds by conversion of Glc-6-P to Glc-1-P to UDP-Glc and is mediated by a phosphoglucomutase (PGM) and a Glc-1-P uridylyltransferase, respectively. Genes encoding both a Glc-1-P uridylyltransferase (cps3U) and a PGM homologue (cps3M) are present in the type 3 capsule locus, but these genes are not essential for capsule production. In this study, we characterized a mutant that produces fourfold less capsule than the type 3 parent. The spontaneous mutation resulting in this phenotype was not contained in the type 3 capsule locus but was instead located in a distant gene (pgm) encoding a second PGM homologue. The function of this gene product as a PGM was demonstrated through enzymatic and complementation studies. Insertional inactivation of pgm reduced capsule production to less than 10% of the parental level. The loss of PGM activity in the insertion mutants also caused growth defects and a strong selection for isolates containing second-site suppressor mutations. These results demonstrate that most of the PGM activity required for type 3 capsule biosynthesis is derived from the cellular PGM.